Investigation of graphene oxide as highly selective adsorbent in recovery of hydroxytyrosol from olive mill wastewater - Sahin, S.; Cigeroglu, Z.; Ozdemir, O. K.; Elhussein, E.; Gulmez, O. (SPRINGER, 2020)
Olive mill wastewater (OMW) is produced in large quantities in the production of olive oil with the three-phase method. This waste, which is not biodegradable and characterized by a heavy organic load containing toxic components (such as phenols), is usually given to aqueous receptors or soil, either directly (untreated) or treated inadequately. Biologically active phenolic compounds that inhibit biodegradation of this waste are toxic at high concentrations, especially for microorganisms, but have positive effects with strong antioxidant properties on human health when properly isolated and properly concentrated.Hydroxytyrosol(HT) is one of the most interesting and abundant compounds among the biophenols present in OMW. According to this study, a newly synthesized nanomaterial, graphene oxide (GO), has been utilized for the separation of HT andtotal biophenolic substancefrom OMW. Graphene oxide from graphite oxidation was synthesized using a modified Hummer's method. In order to understand how GO behaves during thermal degradation, thermogravimetric/differential scanning calorimetry analyses were performed. Two-parameter and three-parameter equilibrium isotherm models and kinetic models have been used to determine the mechanism of kinetic sorption and adsorption type. Thermodynamic data indicate that the adsorption process is exothermic, applicable and spontaneous.
Keywords: Graphene oxide; Adsorption; Hydroxytyrosol; Olive mill wastewater; Biomass; PHENOLIC-COMPOUNDS; AQUEOUS-SOLUTION; ACTIVATED CARBON; ADSORPTION CHARACTERISTICS; CHARCOAL ADSORPTION; REMOVAL; EQUILIBRIUM; BIOSORPTION; NANOSHEETS; OPTIMIZATION; Environmental Sciences & Ecology